Bypassing the EPR effect with a nanomedicine harboring a sustained-release function allows better tumor control - Shen, Yao An (2015)
The current enhanced permeability and retention (EPR)-based approved nanomedicines have had little impact in terms of prolongation of overall survival in patients with cancer. For example, the two Phase III trials comparing Doxil®, the first nanomedicine approved by the US Food and Drug Administration, with free doxorubicin did not find an actual translation of the EPR effect into a statistically significant increase in overall survival but did show less cardiotoxicity. In the current work, we used a two-factor factorial experimental design with intraperitoneal versus intravenous delivery and nanomedicine versus free drug as factors to test our hypothesis that regional (intraperitoneal) delivery of nanomedicine may better increase survival when compared with systemic delivery. In this study, we demonstrate that bypassing, rather than exploiting, the EPR effect via intraperitoneal delivery of nanomedicine harboring a sustained-release function demonstrates dual pharmacokinetic advantages, producing more efficient tumor control and suppressing the expression of stemness markers, epithelial-mesenchymal transition, angiogenesis signals, and multidrug resistance in the tumor microenvironment. Metastases to vital organs (eg, lung, liver, and lymphatic system) are also better controlled by intraperitoneal delivery of nanomedicine than by standard systemic delivery of the corresponding free drug. Moreover, the intraperitoneal delivery of nanomedicine has the potential to replace hyperthermic intraperitoneal chemotherapy because it shows equal efficacy and lower toxicity. In terms of efficacy, exploiting the EPR effect may not be the best approach for developing a nanomedicine. Because intraperitoneal chemotherapy is a type of regional chemotherapy, the pharmaceutical industry might consider the regional delivery of nanomedicine as a valid alternative pathway to develop their nanomedicine(s) with the goal of better tumor control in the future.